Overstory trees in excess: A threat to restoration success in Brazilian Atlantic forest - Cardoso de Oliveira, Carlos Delano [UNESP]; Cardoso de Oliveira, Izabela Regina; Suganuma, Marcio Seiji; Durigan, Giselda (Elsevier B.V., 2019)
Tree planting is the most widely used technique for tropical forest restoration because it accelerates the recovery of forest structure and ecosystem functioning. Despite the importance of tree size distribution to the ecological function and habitat quality of restored forests, it has received little attention. Here we ask if the structure of reference forests has been recovered by planting tree seedlings and discuss the implications of skewed tree-size distributions for sustainability of restored forests. We sampled 11 tropical forest sites that had undergone restoration for between 16 and 53 years after planting tree seedlings and nine reference ecosystems (old-growth, secondary and degraded forests) in Brazilian Atlantic forest, and compared them by the abundance of individuals in five diameter classes. Restored forests presented 83% greater abundance of large trees ( > 20 cm DBH), 41% lower abundance of saplings (1 <= DBH < 5 cm) and 43% lower abundance of small trees (5 <= DBH < 10 cm). The abundance of smaller individuals (DBH < 1 cm), however, did not differ between restored and reference forests, indicating successful colonization of the understorey. Low mortality in the large class (DBH >= 20 cm) results in excess of big trees, which constrains recruitment of small plants to the intermediate size classes, likely due to asymmetric competition for light. The excess of large trees demonstrates that gap dynamics can take longer to naturally re-establish in these even-aged forests, likely due to the high density of long-lived trees planted at the same time. Thinning may be a possible adaptive-management strategy to reduce the density of big trees and stimulate recruitment of intermediate size classes.
Keywords: Asymmetric competition; Carbon balance; Density; Forest structure; Forest restoration; Natural regeneration; Tree size classes; Understorey